A composite phase change film based on liquid metal and PBO fiber and preparation method thereof

By encapsulating OPCMs in the PU wall material and combining them with the PBO fiber network, a special "limited domain" network structure is formed, which solves the problems of easy leakage and low thermal conductivity of solid-liquid PCMs, and significantly improves the thermal stability, mechanical properties and thermal conductivity of the composite phase change film.

CN119490680BActive Publication Date: 2025-04-08SOUTHWEST PETROLEUM UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510080798.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-08
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The application of existing solid-liquid PCMs in efficient thermal management systems is limited by problems such as easy leakage and low thermal conductivity. At the same time, liquid metal Ga has problems such as poor compatibility, easy oxidation and easy leakage in applications.

Method used

A composite phase change film based on liquid metal gallium (Ga) and polyptyrene benzodioxazole fiber (PBO) fiber was prepared by Pickering emulsion polymerization and sol-gel method. By encapsulating organic solid-liquid phase change materials (OPCMs) in the PU wall material and combining them with the PBO fiber network, the dual packaging of OPCMs is achieved, and their dispersion and interaction in the PBO matrix are optimized to form a special "limited domain" network structure.

Benefits of technology

It effectively prevents leakage of OPCMs, significantly enhances the thermal stability, mechanical properties and thermal conductivity of the composite phase change film, and achieves excellent heat storage ability, high strength, excellent in-plane thermal conductivity and stable flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490680B_ABST
    Figure CN119490680B_ABST
Patent Text Reader

Abstract

The present invention is a composite phase change film based on liquid metal and PBO fiber and a preparation method, which belongs to the technical field of phase change material preparation, and includes the following steps: the composite phase change film includes a poly (p-phenylenediazole) fiber (PBO) substrate, a phase change material and a thermal conductive filler, and the phase change material is composed of a phase change microcapsule (PM) prepared by Pickering emulsion polymerization with polyurethane (PU) as the wall material and an organic solid-liquid phase change material (OPCMs) as the core material. The prepared PM has a "core-shell" structure, which effectively prevents the leakage of OPCMs. Combining PM with a PBO fiber network realizes double encapsulation of OPCMs, further preventing the leakage of OPCMs. At the same time, the dispersion and interaction of OPCMs in the PBO matrix are optimized, which promotes the formation of a "confined" network structure. The composite phase change film prepared by the present invention has high mechanical properties, significant thermal conductivity, excellent and stable flexibility and outstanding heat storage capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of phase change material preparation, and in particular to a composite phase change film based on liquid metal and PBO fiber and a preparation method thereof. Background Art

[0002] With the increasing miniaturization of electronic devices and the increasing density of transistors, heat dissipation has become a key bottleneck limiting their performance, stability and long-term reliability. The heat generated by electronic devices during high-load operation is increasingly difficult to dissipate effectively, resulting in local overheating, which not only affects the operating efficiency of the equipment, but may also cause hardware failures, performance degradation, and even shorten the service life of the equipment. At the same time, with the rapid development of environmental camouflage technologies (such as stealth technology and stealth materials), the thermal conductivity of materials faces more stringent requirements. The emergence of high-enthalpy flexible phase change membranes composed of polymer matrices (such as poly(p-phenylenediazole) fiber (PBO), silicone rubber (SR) and polyurethane (PU)) and phase change materials (PCMs) provides an effective and optimal solution to the above challenges. As the core component of phase change membranes, the selection of PCMs has an important influence on the performance of phase change films. Ideal PCMs should have a suitable phase change temperature, high latent heat, good thermal conductivity and excellent thermal stability, while ensuring mechanical strength and chemical stability. Among the widely used PCMs, solid-liquid PCMs represented by n-octadecane (n-OD) have become the preferred materials in the field of modern thermal management and energy storage due to their high specific heat capacity and significant energy storage density. However, solid-liquid PCMs have some inherent defects, such as easy leakage and low thermal conductivity, which to some extent limit their widespread application in efficient thermal management systems.

[0003] Liquid metal (LM), as an emerging metal material, has attracted widespread attention due to its unique physical and chemical properties. In particular, liquid metal gallium (Ga), with its excellent thermal conductivity, high specific heat capacity, excellent fluidity and good plasticity, has great development potential in thermal interface materials, electronic device cooling and other applications with high requirements for thermal management. However, there are still some challenges in the practical application of liquid metal Ga. First, Ga has a high surface tension, which makes it less compatible with the substrate, thereby increasing the difficulty of the preparation process. Secondly, Ga is easily oxidized, and the formation of an oxide layer not only reduces its fluidity, but also affects its thermal conductivity. In addition, it is easy to leak, which may cause failures such as short circuits and corrosion in the application of electronic components, seriously affecting the safety of the equipment. These problems limit its further development in the field of high-end thermal management.

[0004] It has been reported that through phase change microcapsule technology and porous material adsorption technology, solid-liquid PCMs can be encapsulated inside to limit its leakage problem. The Chinese patent with publication number CN 119119970 A discloses a paraffin-based phase change microcapsule and its preparation method. The paraffin-based phase change microcapsule is obtained by dropping a modified alumina aqueous solution into an emulsified solution through in-situ polymerization. The phase change microcapsule has a suitable particle size, low supercooling, and good heat storage (151.1~165.4 J·g -1 ), high thermal conductivity (0.2768~0.3791 W / (m·K)) and can effectively prevent paraffin leakage. The Chinese patent with publication number CN 118852684 A discloses a heterocyclic aramid phase change heat storage film and its preparation method. After the heterocyclic aramid fiber is polymerized at low temperature, the phase change material is coated in situ to obtain an oil-in-oil emulsion, which is then directly water-exchanged and dried to obtain a heterocyclic aramid-based phase change film. The phase change film can effectively prevent the phase change material from leaking during the phase change, and has high latent heat (81.38~167.92J·g -1 ), flame retardancy, temperature resistance, excellent mechanical strength, and outstanding UV shielding and anti-aging properties. However, a single packaging method has certain limitations, which makes solid-liquid PCMs still face a high risk of leakage. In addition, the interfacial interaction between phase change materials and matrix materials is often ignored, which to some extent limits the further development of PCMs in a wider range of applications.

[0005] In order to solve the above-mentioned thorny problems, a Chinese patent with publication number CN 115058058 B discloses a method for preparing a liquid metal-based photothermal phase change energy storage aerogel. Liquid metal and stearic acid are prepared by a simple mechanical ball milling method to prepare a new type of liquid metal-based photothermal phase change particles. At the same time, cellulose aerogel is introduced as a matrix to prepare a liquid metal-based photothermal phase change aerogel with high efficiency in photothermal conversion, anti-leakage, enhanced thermal conductivity (0.2861~0.3095 W / (m·K)) and high energy storage enthalpy (165.5~192.6 J·g -1 ) of liquid metal-based photothermal phase change energy storage aerogel. However, there are still some problems with the LM-enhanced phase change particles prepared by ball milling. First, this method requires a large amount of LM, resulting in high material costs. Secondly, the wettability problem between LM and the matrix material is not fully considered during the vacuum impregnation and freeze-drying gel process, which may affect the bonding strength between the two and the overall performance of the phase change material, thereby limiting its stability in practical applications. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention aims to provide a composite phase change film based on liquid metal and PBO fiber and a preparation method, aiming to solve the inherent problems faced by solid-liquid PCMs in the prior art, such as easy leakage and low thermal conductivity. LM as a thermal conductive filler is easy to oxidize, easy to leak and has poor wettability with the matrix. In addition, excessive use of LM also leads to problems such as increased costs. At the same time, with the help of density functional theory (DFT) and COMSOL simulation, the interfacial interaction between the phase change material and the matrix material and the heat transfer mechanism along the surface of the composite phase change film during heating are respectively explored, which provides a theoretical basis for the mechanical properties and thermal management performance of the composite phase change film in practical applications.

[0007] To solve the above problems, the technical solution of the present invention is as follows:

[0008] The present invention uses n-OD, Ga and PBO nanofibers as raw materials, and adopts Pickering emulsion polymerization and sol-gel method to successfully prepare a composite phase change film based on liquid metal and PBO fiber. Phase change microcapsules (PM) are prepared by using PU as wall material and organic solid-liquid phase change materials (OPCMs) as core material, and PM is combined with PBO fiber network to achieve double encapsulation of OPCMs, effectively preventing the leakage of OPCMs. At the same time, the dispersion and interaction of OPCMs in the PBO matrix are optimized, which promotes the formation of a special "confined" network structure. In addition, CN-modified Ga (MGa) originates from the interaction between CN and Ga nanoparticles, has an optimized size and more uniform distribution in the special "confined" network, and has significant thermal conductivity even at low MGa concentrations.

[0009] The composite phase change film based on liquid metal and PBO fiber and the preparation method thereof described in the present invention specifically include the following steps:

[0010] S1. Sodium dodecyl sulfate (SDS) and deionized water are mixed into a continuous phase, i.e., a water phase; solid-liquid phase change material, isophorone diisocyanate (IPDA) and ethylenediamine (EDA) are heated and stirred to form a uniformly dispersed discontinuous phase, i.e., an oil phase; the oil phase and the water phase are stirred and mixed to form a stable Pickering emulsion system;

[0011] S2, transferring the stable Pickering emulsion system to a three-necked flask for synthesis reaction to form a stable microcapsule solution; after standing and cooling to room temperature, vacuum filtering, washing and drying, PU phase change microcapsules (PM) are obtained;

[0012] S3, stirring and mixing the surface modifier and deionized water to form solution A; adding liquid metal gallium (Ga) to solution A and performing ultrasonic mixing to obtain Ga nano suspension, and obtaining modified Ga nano powder (MGa) after centrifugation, washing and drying; the surface modifier in step S3 is at least one of chitosan quaternary ammonium salt (CN), chitosan (CS), sodium alginate (SA), and tannic acid (TA);

[0013] S4, adding poly(p-phenylene benzobisoxazole) fiber (PBO) micron fiber into a mixed acid of methane sulfonic acid (MSA) and trifluoroacetic acid (TFA), stirring and mixing to obtain a PBO nanofiber solution;

[0014] S5. Disperse MGa and PM in the PBO nanofiber solution, and stir to disperse them evenly; add ethyl acetate (EA) and deionized water, and stir to disperse them evenly to form a mixed PBO viscous sol; pour the viscous sol into a culture dish, and after gelation and aging, obtain an MGa / PM / PBO composite phase change acid gel; after solvent exchange of the acid gel to pH 7, form an MGa / PM / PBO composite phase change hydrogel; after hot pressing and drying the MGa / PM / PBO composite phase change hydrogel, obtain an MGa / PM / PBO composite phase change film.

[0015] As a further improvement of the present invention, in step S1, the solid-liquid phase change material is an organic solid-liquid phase change material (OPCMs), at least one of n-octadecane (n-OD), n-eicosane, and n-tetracosane;

[0016] As a further improvement of the present invention, the mass ratio of the solid-liquid phase change material, IPDA and EDA in step S1 is 3:1:1; the heating and stirring blending is magnetic stirring for 30 minutes at a water bath temperature of 40°C and a rotation speed of 1500 rpm / min; the stirring and mixing is magnetic stirring for 2 to 6 hours at a rotation speed of 15000 rpm / min at 40°C.

[0017] The synthesis reaction in the step S2 is carried out in a 70°C water bath and magnetically stirred at a speed of 300 rpm / min for 3 to 5 hours; the washing in the step S2 is specifically carried out 2 to 5 times, and the solvent used for washing is deionized water; the drying in the step S2 is carried out in a forced air drying oven at a temperature of 50°C for 24 to 48 hours; the mass ratio of the wall material (PU) to the core material (OPCMs) of the PM is (0.5 to 4):1.

[0018] As a further improvement of the present invention, the surface modifier in step S3 is at least one of chitosan quaternary ammonium salt (CN), chitosan (CS), sodium alginate (SA), and tannic acid (TA); the stirring and mixing described in step S3 is specifically performed at room temperature, with a rotation speed of 400 rpm and a magnetic stirring time of 10 to 30 min; the concentration of solution A described in step S3 is 0, 0.3, 0.4, 0.6 or 0.9 mg / ml; the ultrasound described in step S3 is performed in an ice water bath with a power of 500 W, a time of 1 to 4 h, and a Ga nanosuspension concentration of 1 wt%; the washing described in step S3 is specifically performed 2 to 5 times, and the solvent used is deionized water; the drying environment described in step S3 is a vacuum condition, a pressure of -0.1 MPa, a temperature of 50°C, and a time of 24 to 48 h.

[0019] The mass ratio of MSA and TFA mixed acid in step S4 is 1:1; the stirring and mixing in step S4 is specifically performed under room temperature, with a rotation speed of 400 rpm and a mechanical stirring time of 36 to 72 hours; the concentration of the PBO nanofiber solution is 0.5wt%;

[0020] In the step S5, the mass ratio of MGa, PM and PBO nanofibers is one of 0:5:1, 0.2:5:1, 0.5:5:1, 1:5:1, 2:5:1 or 3:5:1; the specific conditions for stirring and dispersing in the step S5 are mechanical stirring at a rotation speed of 350-400 rpm for 5-10 min; the gelation and aging in the step S5 are respectively standing for 2 h and 20-24 h at room temperature; the solvent exchange in the step S5 is first replaced under 30-70 wt% MSA acidic conditions for 20-40 h, and then solvent exchange is performed using deionized water for 36-48 h, during which the solvent is replaced every 4 h; the hot pressing drying in the step S5 is carried out in a blast drying oven at a pressure of 0.1-0.5 MPa, a temperature of 60-80°C, and a time of 24-36 h.

[0021] As a further improvement of the present invention, the composite phase change film based on liquid metal and PBO fiber comprises a PBO nanofiber substrate, a phase change material and a thermal conductive filler; the composite phase change film has a "confined" network structure.

[0022] As a further improvement of the present invention, the phase change material of the composite phase change film based on liquid metal and PBO fiber is a phase change microcapsule; the phase change microcapsule is composed of polyurethane (PU) as wall material and OPCMs n-octadecane (n-OD) as core material, and has a size of 5~10 μm; the phase change microcapsule has a "core-shell" structure.

[0023] As a further improvement of the present invention, in the composite phase change film based on liquid metal and PBO fiber, the thermal conductive filler is composed of liquid metal modified by a surface modifier, and the particle size is 100~700nm; the surface modifier is chitosan quaternary ammonium salt (CN), and the liquid metal is metallic gallium (Ga); the thermal conductive filler has a "core-shell" structure.

[0024] As a further improvement of the present invention, the composite phase change film based on liquid metal and PBO fiber, the MGa / PM / PBO composite phase change film has excellent heat storage capacity, and the maximum heat storage performance is 140.8 J·g -1 , the maximum strength is 7MPa, and it has excellent and stable flexibility.

[0025] As a further improvement of the present invention, the composite phase change film based on liquid metal and PBO fiber has an in-plane thermal conductivity of 2.9422 W / (m·K) in the composite phase change film with an "island" structure, and a in-plane thermal conductivity of 5.2982~11.5387 W / (m·K) in the composite phase change film with a "confined" network structure.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention adopts Pickering emulsion polymerization to prepare phase change microcapsules (PM), and encapsulates organic solid-liquid phase change materials (OPCMs) n-octadecane (n-OD) by polyurethane (PU). The prepared PM has a high phase change enthalpy value (163.7 J·g -1 ) and good anti-leakage ability; further combining PM with PBO fiber network, optimizing the dispersion and interaction of n-OD in PBO matrix. At the same time, it also facilitates the formation of a special "confined" network structure. In addition, the dual encapsulation strategy adopted effectively suppresses the leakage problem of phase change materials and significantly enhances the thermal stability, mechanical properties and thermal conductivity of the composite phase change film.

[0028] (2) The present invention adopts a simple ultrasonic process to prepare thermal conductive fillers, and the liquid metal gallium (Ga) wrapped by the surface modifier chitosan quaternary ammonium salt (CN) can effectively prevent Ga from being oxidized to gallium oxyhydroxyl ((GaO)OH) in aqueous solution. At the same time, the liquid metal nanoparticles prepared by the present invention have a "core-shell" structure, with a particle size of 100~700nm. The liquid metal nanosuspension has good colloidal stability and can be stably suspended in water for more than 48 hours. In addition, because MGa exhibits an optimized size and more uniform dispersion in a special "confined" network structure, it can achieve excellent thermal conductivity even at lower concentrations.

[0029] (3) The composite phase change film prepared by the present invention has excellent heat storage capacity (87.1~140.8 J·g -1 ), high strength (7MPa), excellent in-plane thermal conductivity (5.2982~11.5387 W / (m·K)), excellent and stable flexibility and good thermal stability.

[0030] (4) The present invention uses density functional theory (DFT) and COMSOL simulation to explore the interfacial interaction between the phase change material and the matrix material and the heat transfer mechanism along the surface of the composite phase change film during heating, respectively, providing a theoretical basis for the mechanical properties and thermal management performance of the composite phase change film in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention is a preparation flow chart of a method for preparing a composite phase change film based on liquid metal and PBO fiber.

[0032] Figure 2 (a), (b) and (c) are scanning electron microscopy (SEM), polarizing microscopy and particle size distribution diagrams of PM prepared in Example 1, respectively.

[0033] Figure 3 (a), (b) and (c) are the actual images, X-ray diffraction analysis (XRD) and particle size analysis of Ga and MGa suspensions prepared in Example 1, respectively; (d), (e) and (f) are the SEM and energy dispersive spectrometer (EDS) images of MGa nanoparticles prepared in Example 1, respectively.

[0034] Figure 4 (a), (b), (c) and (d) represent the SEM images corresponding to the cross-sections of the composite phase change films prepared in Comparative Example 7, Comparative Example 6, Comparative Example 3 and Example 1, respectively; (e) and (f) are the EDS and locally enlarged SEM images of the MGa / PM / PBO composite phase change film prepared in Example 1.

[0035] Figure 5 (a) and (b) respectively represent the thermal conductivity performance diagrams of the composite phase change films prepared in Examples 1 to 5, Comparative Example 3, Comparative Example 6 and Comparative Example 7.

[0036] Figure 6 (a), (b), (c) and (d) are Comsol simulation schematic diagrams of the heat transfer process of the MGa / PBO and MGa / PM / PBO composite films prepared in Comparative Example 8 and Example 1.

[0037] Figure 7(a) is the stress-strain curve of Example 1, Comparative Examples 3 and 6; (b) and (c) are density functional theory (DFT) simulation and result diagrams of the interface interaction between the phase change material and the matrix material in the composite phase change films prepared in Example 1 and Comparative Example 6. DETAILED DESCRIPTION

[0038] The present invention provides a composite phase change film based on liquid metal and PBO fiber and a preparation method thereof. In order to make the purpose, technical solution and advantages of the present invention clearer and more specific, the present invention is further described in conjunction with specific embodiments and drawings.

[0039] Example 1

[0040] like Figure 1 As shown, a composite phase change film based on liquid metal and PBO fiber and a preparation method of the present invention are prepared by the following steps:

[0041] Step 1: Dissolve 1.5 g sodium dodecyl sulfate (SDS) and 100 g deionized water and mix them evenly to form a continuous phase, i.e., the water phase; melt 15.0 g n-octadecane (n-OD) at 40 °C, add 5 g isophorone diisocyanate (IPDA) and 5 g ethylenediamine (EDA), and stir magnetically for 30 min at a water bath temperature of 40 °C and a rotation speed of 1500 rpm / min to form a uniformly dispersed discontinuous phase, i.e., the oil phase; add the oil phase liquid drop by drop into the water phase, and stir magnetically for 4 h at a water bath temperature of 40 °C and a rotation speed of 1500 rpm / min to form a stable Pickering emulsion system;

[0042] Step 2: The Pickering emulsion system obtained in step 1 was transferred to a three-necked flask, and magnetically stirred for 3.5 h at a water bath temperature of 70 °C and a rotation speed of 300 rpm / min to form a stable microcapsule solution; the reaction microcapsule solution was allowed to stand and naturally cool to room temperature (25-30 °C), then vacuum filtered, washed with deionized water for 2-5 times, and dried in a forced air drying oven at 50 °C for 36 h to obtain PU phase change microcapsules (PM).

[0043] Step 3: Add 9.0 mg of chitosan quaternary ammonium salt (CN) to 15 ml of deionized water, and stir magnetically for 20 min at room temperature at a speed of 400 rpm to obtain a CN aqueous solution with a mass fraction of 0.6 wt%; add 150 mg of liquid metal gallium (Ga) to the CN aqueous solution, and ultrasonicate at a power of 500 W for 2 h in an ice water bath to form a uniform modified Ga (MGa) nanosuspension, and then centrifuge and wash with deionized water for 2 to 5 times, and then place in a vacuum oven at a pressure of -0.1 MPa and a temperature of 50 ° C for 24 h to obtain MGa powder;

[0044] Step 4: 1.0 g of poly(p-phenylene benzobisoxazole) fiber (PBO) micron fiber was added to a mixed acid of 100 g of methane sulfonic acid (MSA) and 100 g of trifluoroacetic acid (TFA), and mechanically stirred at 400 rpm for 48 h at room temperature to obtain a PBO nanofiber solution with a mass fraction of 0.5 wt%;

[0045] Step 5: Add 0.05 g MGa and 0.25 g PM to 10.0 g PBO solution with a mass fraction of 0.5 wt%, and stir mechanically at a speed of 380 pm for 5 min to obtain a mixed PBO solution; mix 4.0 g ethyl acetate (EA) and 0.5 g deionized water evenly, add dropwise to the mixed PBO solution, and stir mechanically at a speed of 380 pm for 10 min to obtain a mixed PBO viscous sol;

[0046] Step 6: Pour the mixed PBO viscous sol into a culture dish and let it stand at room temperature for 4 h of gelation and 20 h of aging to obtain an MGa / PM / PBO composite phase change acid gel; soak the acid gel in a 70 wt % MSA aqueous solution to exchange the solvent for 12 h, and then exchange it in a 30 wt % MSA aqueous solution for another 12 h, and then soak the gel in deionized water to exchange the solvent for 72 h, during which the solvent is replaced every 4 h to obtain an MGa / PM / PBO composite phase change hydrogel; then, the hydrogel is hot-pressed and dried in a 70 °C forced air drying oven at a pressure of 0.3 MPa for 24 h to obtain an MGa / PM / PBO composite phase change film.

[0047] The phase change microcapsules (PM) prepared in Example 1 were analyzed by scanning electron microscopy, polarizing microscopy and laser particle size test, and the results were as follows: Figure 2 As shown in (a), (b) and (c).

[0048] Figure 2The successful preparation of phase change microcapsules (PM) by encapsulating n-octadecane (n-OD) with polyurethane (PU) was revealed. The average particle size (d) of the PM was 6.841 μm, showing an obvious "core-shell" structure, which effectively encapsulated n-OD and inhibited the leakage of the phase change material.

[0049] The MGa nanosuspension prepared in Example 1 was subjected to physical observation, and the prepared MGa particles were subjected to physical observation, X-ray diffraction analysis (XRD), particle size analysis test, scanning electron microscopy and energy spectrum analysis, and the results are as follows: Figure 3 As shown in (a), (b), (c), (d), (e) and (f).

[0050] Figure 3 It is revealed that the introduction of CN can effectively promote the dispersion of Ga, and its particle size is reduced from 680nm (Ga) to 148nm (MGa). The actual objects before and after ultrasound are as follows Figure 3 (a) As shown on the left and right, the particle size distribution is as follows Figure 3 (c) In addition, the introduction of CN effectively prevents the further oxidation of Ga in aqueous solution and has a good encapsulation effect on it. The results are shown in Figure 3 As shown in (b), (d), (e) and (f).

[0051] Embodiments 2 to 5

[0052] Examples 2 to 5 provide a composite phase change film based on liquid metal and PBO fiber and a preparation method. Compared with Example 1, the difference is that in step 5, the mass ratios of MGa, PM and PBO nanofibers are 0.2:5:1, 0.5:5:1, 2:5:1 and 3:5:1, and the rest are the same as Example 1 and will not be repeated here.

[0053] Comparative Examples 1 to 5

[0054] Comparative Examples 1 to 5 provide a composite phase change film based on liquid metal and PBO fiber and a preparation method. Compared with Example 1, the difference is that step 3 is removed and MGa is not added in step 5. At the same time, the mass ratio of PM and PBO nanofibers is 1:1, 3:1, 5:1, 7:1 and 10:1. The rest is the same as Example 1 and will not be repeated here to obtain a PM / PBO composite phase change film.

[0055] Comparative Example 6

[0056] Comparative Example 6 provides a composite phase change film based on liquid metal and PBO fiber and a preparation method. Compared with Example 1, the difference is that steps 1 to 3 are removed, MGa is not added in step 5, and PM is changed to pure n-OD. The rest is the same as Example 1 and will not be repeated here to obtain an n-OD / PBO composite phase change film.

[0057] Comparative Example 7

[0058] Comparative Example 7 provides a composite phase change film based on liquid metal and PBO fiber and a preparation method. Compared with Example 1, the difference is that steps 1 to 3 are removed, and PM and MGa are not added in step 5. The rest is the same as Example 1 and will not be repeated here to obtain a pure PBO film.

[0059] Comparative Example 8

[0060] Comparative Example 8 provides a composite phase change film based on liquid metal and PBO fiber and a preparation method. Compared with Example 1, the difference is that steps 1~2 are removed and MGa is not added in step 5. The rest is the same as Example 1 and will not be repeated here to obtain an MGa / PBO film.

[0061] The cross-sectional morphology of the composite phase change films prepared in Example 1 and Comparative Examples 3, 6 and 7 was observed by scanning electron microscopy. The pure PBO film had a dense structure and an obvious pearl-like structure ( Figure 4 (a) There is a significant macroporous structure in the n-OD / PBO composite phase change film and the n-OD is unevenly distributed, with an "island-like" structure ( Figure 4 (b) The PM / PBO and MGa / PM / PBO composite phase change films have dense structures, PM is evenly dispersed inside the PBO film, and the PM surface is covered by the PBO nanofiber network ( Figure 4 (c) and (d)). The introduction of PM optimizes the dispersion and interaction of MGa and n-OD in the PBO matrix and also promotes the formation of a special "confined" network structure ( Figure 4 (e) and (f)).

[0062] The composite phase change films prepared in Examples 1 to 5 and Comparative Examples 1 to 8 were tested for their thermophysical properties using a differential scanning calorimeter (DSC) from TA Corporation of the United States (heating rate of 5°C / min, temperature range of -10 to 60°C). The test results are shown in the following table:

[0063] Table 1 Thermophysical properties test results of composite phase change films

[0064] Sample name <![CDATA[T m (℃)]]> <![CDATA[T c (℃)]]> <![CDATA[ΔH m (J·g -1 )]]> <![CDATA[ΔH c (J·g -1 )]]> Comparative Example 1 28.3 18.9 25.6 24.3 Comparative Example 2 29.6 21.7 83.0 84.1 Comparative Example 3 29.96 21.82 105.5 107.4 Comparative Example 4 30.7 22.2 106.7 108.2 Comparative Example 5 30.5 22.3 132.1 131.2 Comparative Example 6 29.0 22.9 133.1 137.5 Comparative Example 7 / / / / Comparative Example 8 / / / / Example 2 29.33 21.94 104.1 106.3 Example 3 29.72 21.47 107. 1 108.6 Example 1 30.43 21.45 100.9 100.4 Example 4 29.64 21.41 91.8 93.1 Example 5 29.82 21.49 87.1 87.7

[0065] From the data in Table 1, it can be seen that with the increase of PM content, the phase change enthalpy values ​​of the composite films of Comparative Examples 1 to 5 gradually increase (from 25.6 J·g -1 Increased to 133.1 J·g -1 ), this change is mainly attributed to the increase in the content of the working medium involved in the phase change. However, when the PM content is too high, the flexibility of the composite film decreases significantly, and it is easy to break when subjected to external pressure. With the increase of MGa content, the enthalpy values ​​of the composite phase change films of Examples 1 to 5 gradually decrease. When the MGa loading is less than 14.3wt%, the melting enthalpy and crystallization enthalpy (ΔH c ) is basically the same as that of Comparative Example 3. Although the ΔH of the composite phase change film of Example 1 m and ΔH c Compared with comparative example 6, the -1 and 137.5 J·g -1 Down to 100.9 J·g -1 and 100.4 J·g -1 , but its heat storage capacity can still meet the needs of thermal management applications.

[0066] The composite phase change films prepared in Examples 1 to 5 and Comparative Examples 3, 6 and 7 were tested for thermal conductivity using a laser thermal conductivity meter. The test results are as follows: Figure 5 (a) and (b). Compared with the thermal conductivity of pure n-OD (0.153 W / (m·K)), the thermal conductivity of the composite phase change film is significantly improved. This improvement is mainly attributed to the excellent thermal conductivity of the PBO film itself, among which the vertical thermal conductivity (k ⊥ ) and the in-plane thermal conductivity (k ∥ ) are 0.9520 W / (m·K) and 2.9483 W / (m·K), respectively. In addition, with the increase of PM and thermal conductive filler MGa content, the k of the composite phase change film increases. ⊥ and k ∥ When the MGa content is 14.3wt%, the k of the composite phase change film in Example 1 ⊥ and k ∥ Reaching 3.1482 and 9.4752 W / (m·K) respectively. The main reasons for the significant improvement in thermal conductivity are: First, the introduction of PM optimizes the dispersion and interaction of MGa in the PBO matrix, and also promotes the formation of a special "confined" network structure, which significantly enhances the thermal conduction channel of the film and promotes efficient heat transfer. Even in the case of high PM load and low MGa load, the composite phase change film can still maintain excellent thermal conductivity. Secondly, the introduction of MGa improves the interface interaction between PM and PBO, weakens the phonon scattering effect at the interface, and thus effectively improves the thermal conductivity.

[0067] The composite films prepared in Comparative Example 8 and Example 1 were simulated by Comsol to find out the heat transfer mechanism along the surface during heating. The results are as follows: Figure 6 (a), (b), (c) and (d). In the Comsol simulation results, the thermal conductivity of the MGa / PM / PBO composite phase change film is significantly improved. This is mainly attributed to the formation of a special "confined" network structure between PBO nanofibers and MGa in the presence of a high content of PM. This structure significantly improves the efficiency of heat transfer by enhancing the thermal contact between adjacent components.

[0068] The mechanical properties of the composite phase change films prepared in Example 1, Comparative Example 3 and Comparative Example 6 were measured by a universal tensile testing machine, and the interface interaction between the phase change material and the matrix material was theoretically analyzed by density functional theory (DFT) simulation. The results are as follows: Figure 7 (a), (b) and (c). The results show that the introduction of PM optimizes the dispersion and interaction of n-OD in the PBO matrix and forms a special "confined" network structure, which significantly improves the mechanical properties of the film (tensile strength increases from 2.63MPa to 6.15MPa). At the same time, it promotes the optimized size and more uniform dispersion of MGa in the special "confined" network structure, further improving its mechanical properties (tensile strength is 7.0 MPa). In addition, density functional theory (DFT) simulations show that the binding energy between PBO and PM is stronger than that between n-OD and the PBO substrate.

[0069] In summary, the present invention successfully prepared a composite phase change film based on liquid metal and PBO fiber by using Pickering emulsion polymerization and sol-gel method. Phase change microcapsules (PM) were prepared by using PU as wall material and OPCMs as core material, and PM was combined with PBO fiber network to achieve double encapsulation of OPCMs, effectively preventing leakage of OPCMs. At the same time, the dispersion and interaction of OPCMs in the PBO matrix were optimized, which led to the formation of a special "confined" network structure. In addition, CN-modified Ga (MGa) originates from the interaction between CN and Ga nanoparticles, has an optimized size and more uniform distribution in the confined network, and has significant thermal conductivity even at low MGa concentrations. Based on this, the composite phase change film (MGa / PM / PBO) exhibits excellent heat storage capacity (87.1~140.8 J·g -1), high strength (7MPa), excellent in-plane thermal conductivity (5.2982~11.5387 W / (m·K)), excellent and stable flexibility and good thermal stability. Overall, the present invention introduces a new method for preparing high-performance phase change films, which has obvious advantages in electronic equipment heat dissipation and other high-end thermal management applications.

Claims

1. A method for preparing a composite phase change film based on liquid metal and PBO fiber, characterized in that: The following steps are involved: S1, mixing sodium dodecyl sulfate and deionized water into a continuous phase, i.e., an aqueous phase; heating and stirring a solid-liquid phase change material, isophorone diisocyanate and ethylenediamine to form a uniformly dispersed discontinuous phase, i.e., an oil phase; stirring and mixing the oil phase and the aqueous phase to form a stable Pickering emulsion system; The solid-liquid phase change material in step S1 is an organic solid-liquid phase change material, specifically one of n-octadecane, n-eicosane, and n-tetracosane; the mass ratio of the solid-liquid phase change material, isophorone diisocyanate, and ethylenediamine is 3:1:1; the heating, stirring, and blending in step S1 are specifically performed under the conditions of a water bath temperature of 40°C, a rotation speed of 1500 rpm / min, and magnetic stirring for 30 minutes; the stirring and mixing in step S1 are specifically performed under the conditions of a water bath temperature of 40°C, a rotation speed of 1500 rpm / min, and magnetic stirring for 2-6 hours; S2, transferring the stable Pickering emulsion system to a three-necked flask for synthesis reaction to form a stable microcapsule solution; after standing and cooling to room temperature, vacuum filtering, washing and drying, polyurethane phase change microcapsules are obtained; The synthesis reaction in step S2 is carried out in a 70°C water bath and magnetically stirred at a speed of 300 rpm / min for 3 to 5 hours; the washing in step S2 is specifically carried out 2 to 5 times, and the solvent used for washing is deionized water; the drying in step S2 is carried out in a blast drying oven at a temperature of 50°C for 24 to 48 hours; the mass ratio of the wall material to the core material of the phase change microcapsule is 0.5:1; S3, stirring and mixing the surface modifier and deionized water to form solution A; adding liquid metal gallium to solution A and performing ultrasonic mixing to obtain a liquid metal gallium nanosuspension, and obtaining a modified liquid metal gallium nanopowder after centrifugation, washing and drying; The surface modifier in step S3 is at least one of chitosan quaternary ammonium salt, chitosan, sodium alginate, and tannic acid; the stirring and mixing in step S3 is specifically performed at room temperature, with a rotation speed of 400 rpm and a magnetic stirring time of 10 to 30 min; the concentration of solution A in step S3 is 0.3, 0.4, 0.6 or 0.9 mg / ml; the ultrasound in step S3 is performed in an ice water bath with a power of 500 W, a time of 1 to 4 h, and a Ga nanosuspension concentration of 1 wt%; the washing in step S3 is specifically performed 2 to 5 times, and the solvent used is deionized water; the drying environment in step S3 is a vacuum condition, with a pressure of -0.1 MPa, a temperature of 50°C, and a time of 24 to 48 h; S4, adding poly(p-phenylene benzobisoxazole) fiber micron fibers into a mixed acid of methanesulfonic acid and trifluoroacetic acid, stirring and mixing to obtain a PBO nanofiber solution; The mass ratio of methanesulfonic acid to trifluoroacetic acid in step S4 is 1:1; the stirring and mixing in step S4 is specifically performed under room temperature, with a rotation speed of 400 rpm and a mechanical stirring time of 36 to 72 hours; the concentration of the PBO nanofiber solution is 0.5wt%; S5, dispersing the modified liquid metal gallium nanopowder and phase change microcapsules in the PBO nanofiber solution, stirring and dispersing them evenly; adding ethyl acetate and deionized water thereto, stirring and dispersing them evenly to form a mixed PBO viscous sol; pouring the viscous sol into a culture dish, gelling and aging it to obtain a MGa / PM / PBO composite phase change acid gel; replacing the acid gel with a solvent to a pH of 7 to form a MGa / PM / PBO composite phase change hydrogel; hot pressing and drying the MGa / PM / PBO composite phase change hydrogel to obtain a MGa / PM / PBO composite phase change film; In the step S5, the mass ratio of the modified liquid metal gallium nanopowder, phase change microcapsule and PBO nanofiber is one of 0.2:5:1, 0.5:5:1, 1:5:1, 2:5:1 or 3:5:1; the specific conditions for stirring and dispersing in the step S5 are mechanical stirring at a rotation speed of 350-400 rpm for 5-10 min; the gelation and aging in the step S5 are respectively standing for 2 h and 20-24 h at room temperature; the solvent exchange in the step S5 is first replaced under 30-70wt% MSA acidic conditions for 20-40 h, and then solvent exchange is performed using deionized water for 36-48 h, during which the solvent is replaced every 4 h; the hot pressing drying in the step S5 is carried out in a blast drying oven at a pressure of 0.1-0.5 MPa, a temperature of 60-80°C, and a time of 24-36 h.

2. A composite phase change film based on liquid metal and PBO fiber, characterized in that: The preparation method according to claim 1 is used to obtain the 3. The composite phase change film based on liquid metal and PBO fiber according to claim 2, characterized in that: The composite phase change film comprises a PBO nanofiber substrate, a phase change material and a thermal conductive filler; the composite phase change film has a "confined domain" network structure.

4. The composite phase change film based on liquid metal and PBO fiber according to claim 2, characterized in that: The phase change material is a phase change microcapsule; the phase change microcapsule is composed of polyurethane as the wall material and OPCMs n-octadecane as the core material, and has a size of 5-10 μm; the phase change microcapsule has a "core-shell" structure.

5. The composite phase change film based on liquid metal and PBO fiber according to claim 2, characterized in that: The thermal conductive filler is composed of liquid metal modified by a surface modifier, and the particle size is 100-700nm; the surface modifier is chitosan quaternary ammonium salt, and the liquid metal is metallic gallium; the thermal conductive filler has a "core-shell" structure.

6. The composite phase change film based on liquid metal and PBO fiber according to claim 2, characterized in that: The maximum heat storage performance of the MGa / PM / PBO composite phase change film is 140.8 J·g -1 , the maximum strength is 7MPa.

7. The composite phase change film based on liquid metal and PBO fiber according to claim 2, characterized in that: The thermal conductivity of the composite phase change film with a "confined domain" network structure in the composite phase change film is 5.2982~11.5387 W / (m·K).

Citation Information

Patent Citations

  • A method for preparing liquid metal-based photothermal phase change energy storage aerogel

    CN115058058B

  • Heterocyclic aramid fiber phase change heat storage film and preparation method thereof

    CN118852684A

  • Paraffin-based phase change microcapsule and preparation method thereof

    CN119119970A

  • Super-hydrophobic microcapsule made from phase-change materials and preparation method of super-hydrophobic microcapsule

    CN104927779A

  • Inorganic composite phase-change energy storage material and preparation method thereof

    CN111154457A